Assessment of economic efficiency of artificial intelligence application in construction: the choice of the optimal method - D. N. Shishkina (Vestnik MGSU)
Introduction. The review of existing ideas of artificial intelligence implementation in the construction industry is carried out. On the basis of the studied data the applicability of the technologies was analyzed and their economic efficiency was evaluated, as well as the feasibility of investment in potential projects was substantiated. Construction is a fundamental area of human life, in which the use of information technology innovations, especially artificial intelligence should be associated with a balanced decision and thorough testing. For this reason, it is required to choose the most appropriate method to evaluate the feasibility of implementation. By the chosen method it is possible to reveal the possibilities of a new project and to correlate it with all costs and risks.Materials and methods. Russian and foreign studies, Internet resources and conference materials were studied. As a result, the current trends of technologies of artificial intelligence application in construction were found. The integrated method allowed to consider technologies from the point of view of ideology, reality of embodiment, practical application and economic feasibility. The method of scoring of projects was applied and the list of technologies was compiled. This list includes technologies that are favourable for application and promising for development. Multilevel study of the selected projects was carried out according to the system modelling approach.Results. Based on the results of the study, conclusions are made about the best method for assessing the economic efficiency of innovative projects based on artificial intelligence, which are applicable to the construction industry. The theoretical model is aimed at considering the project as a process of cause-and-effect relationships. This project reveals the list of necessary steps and their sequence.Conclusions. This study on the effectiveness of the implementation of AI in construction of some ideas revealed an optimal and sufficiently informative method of assessing the economic efficiency of projects, as well as the degree of relevance and compliance with the interests and needs of the construction industry. A list of recommendations for the process of implementation of a new project with the use of artificial intelligence is presented. A vector for further research in the field of practical calculations of efficiency and forecasting is proposed.